Difference between revisions of "2013 AIME I Problems/Problem 14"
Alexlikemath (talk | contribs) |
Hashtagmath (talk | contribs) |
||
(One intermediate revision by the same user not shown) | |||
Line 1: | Line 1: | ||
− | == Problem | + | == Problem == |
For <math>\pi \le \theta < 2\pi</math>, let | For <math>\pi \le \theta < 2\pi</math>, let | ||
Line 14: | Line 14: | ||
so that <math>\frac{P}{Q} = \frac{2\sqrt2}{7}</math>. Then <math>\sin\theta = -\frac{m}{n}</math> where <math>m</math> and <math>n</math> are relatively prime positive integers. Find <math>m+n</math>. | so that <math>\frac{P}{Q} = \frac{2\sqrt2}{7}</math>. Then <math>\sin\theta = -\frac{m}{n}</math> where <math>m</math> and <math>n</math> are relatively prime positive integers. Find <math>m+n</math>. | ||
− | + | ==Solution 1== | |
− | |||
Noticing the <math>\sin</math> and <math>\cos</math> in both <math>P</math> and <math>Q,</math> we think of the angle addition identities: <cmath>\sin(a + b) = \sin a \cos b + \cos a \sin b, \cos(a + b) = \cos a \cos b + \sin a \sin b.</cmath> With this in mind, we multiply <math>P</math> by <math>\sin \theta</math> and <math>Q</math> by <math>\cos \theta</math> to try and use some angle addition identities. Indeed, we get | Noticing the <math>\sin</math> and <math>\cos</math> in both <math>P</math> and <math>Q,</math> we think of the angle addition identities: <cmath>\sin(a + b) = \sin a \cos b + \cos a \sin b, \cos(a + b) = \cos a \cos b + \sin a \sin b.</cmath> With this in mind, we multiply <math>P</math> by <math>\sin \theta</math> and <math>Q</math> by <math>\cos \theta</math> to try and use some angle addition identities. Indeed, we get | ||
Line 26: | Line 25: | ||
This is a system of equations; rearrange and rewrite to get <cmath>P(1 + 2 \sin \theta) + 2Q \cos \theta = 2 \cos \theta</cmath> and <cmath>P \cos^2 \theta + Q \cos \theta(2 + \sin \theta) = 2 \cos \theta.</cmath> Subtract the two and rearrange to get <cmath>\dfrac{P}{Q} = \dfrac{\cos \theta}{2 + \sin \theta} = \dfrac{2 \sqrt{2}}{7}.</cmath> Then, square both sides and use Pythagorean Identity to get a quadratic in <math>\sin \theta.</math> Factor that quadratic and solve for <math>\sin \theta = -17/19, 1/3.</math> The answer format tells us it's the negative solution, and our desired answer is <math>17 + 19 = \boxed{036}.</math> | This is a system of equations; rearrange and rewrite to get <cmath>P(1 + 2 \sin \theta) + 2Q \cos \theta = 2 \cos \theta</cmath> and <cmath>P \cos^2 \theta + Q \cos \theta(2 + \sin \theta) = 2 \cos \theta.</cmath> Subtract the two and rearrange to get <cmath>\dfrac{P}{Q} = \dfrac{\cos \theta}{2 + \sin \theta} = \dfrac{2 \sqrt{2}}{7}.</cmath> Then, square both sides and use Pythagorean Identity to get a quadratic in <math>\sin \theta.</math> Factor that quadratic and solve for <math>\sin \theta = -17/19, 1/3.</math> The answer format tells us it's the negative solution, and our desired answer is <math>17 + 19 = \boxed{036}.</math> | ||
− | + | ==Solution 2== | |
Use sum to product formulas to rewrite <math>P</math> and <math>Q</math> | Use sum to product formulas to rewrite <math>P</math> and <math>Q</math> | ||
Line 41: | Line 40: | ||
Then use the pythagorean identity to solve for <math>\sin\theta</math>, <math>\sin\theta = -\frac{17}{19} \implies \boxed{036}</math> | Then use the pythagorean identity to solve for <math>\sin\theta</math>, <math>\sin\theta = -\frac{17}{19} \implies \boxed{036}</math> | ||
− | + | ==Solution 3== | |
Note that <cmath>e^{i\theta}=\cos(\theta)+i\sin(\theta)</cmath> | Note that <cmath>e^{i\theta}=\cos(\theta)+i\sin(\theta)</cmath> | ||
Line 71: | Line 70: | ||
<math>017+019=\boxed{036}</math> | <math>017+019=\boxed{036}</math> | ||
− | + | ==Solution 4== | |
A bit similar to Solution 3. We use <math>\phi = \theta+90^\circ</math> because the progression cycles in <math>P\in (\sin 0\theta,\cos 1\theta,-\sin 2\theta,-\cos 3\theta\dots)</math>. So we could rewrite that as <math>P\in(\sin 0\phi,\sin 1\phi,\sin 2\phi,\sin 3\phi\dots)</math>. | A bit similar to Solution 3. We use <math>\phi = \theta+90^\circ</math> because the progression cycles in <math>P\in (\sin 0\theta,\cos 1\theta,-\sin 2\theta,-\cos 3\theta\dots)</math>. So we could rewrite that as <math>P\in(\sin 0\phi,\sin 1\phi,\sin 2\phi,\sin 3\phi\dots)</math>. | ||
Line 93: | Line 92: | ||
Since <math>y<0</math> because <math>\pi<\theta<2\pi</math>, <math>y=\sin\theta=-\frac{51}{57}=-\frac{17}{19}</math>. Adding up, <math>17+19=\boxed{036}</math>. | Since <math>y<0</math> because <math>\pi<\theta<2\pi</math>, <math>y=\sin\theta=-\frac{51}{57}=-\frac{17}{19}</math>. Adding up, <math>17+19=\boxed{036}</math>. | ||
− | + | ==Solution 5 (lots of room for sillies, I wouldn't recommend it)== | |
We notice <math>\sin\theta=\frac{-i}{2}(e^{i\theta}-e^{-i\theta})</math> and <math>\cos\theta=\frac{1}{2}(e^{i\theta}+e^{-i\theta})</math> | We notice <math>\sin\theta=\frac{-i}{2}(e^{i\theta}-e^{-i\theta})</math> and <math>\cos\theta=\frac{1}{2}(e^{i\theta}+e^{-i\theta})</math> | ||
Line 107: | Line 106: | ||
omg this was definitely the hardest problem on the AIME I | omg this was definitely the hardest problem on the AIME I | ||
− | + | ==Solution 6== | |
Follow solution 3, up to the point of using the geometric series formula | Follow solution 3, up to the point of using the geometric series formula | ||
<cmath>Q+iP=\frac{1}{1+\frac{\sin(\theta)}{2}-\frac{Qi\cos(\theta)}{2}}</cmath> | <cmath>Q+iP=\frac{1}{1+\frac{\sin(\theta)}{2}-\frac{Qi\cos(\theta)}{2}}</cmath> |
Latest revision as of 19:13, 24 January 2021
Contents
Problem
For , let
and
so that . Then where and are relatively prime positive integers. Find .
Solution 1
Noticing the and in both and we think of the angle addition identities: With this in mind, we multiply by and by to try and use some angle addition identities. Indeed, we get after adding term-by-term. Similar term-by-term adding yields This is a system of equations; rearrange and rewrite to get and Subtract the two and rearrange to get Then, square both sides and use Pythagorean Identity to get a quadratic in Factor that quadratic and solve for The answer format tells us it's the negative solution, and our desired answer is
Solution 2
Use sum to product formulas to rewrite and
Therefore,
Using
Plug in to the previous equation and cancel out the "P" terms to get: .
Then use the pythagorean identity to solve for ,
Solution 3
Note that
Thus, the following identities follow immediately:
Consider, now, the sum . It follows fairly immediately that:
This follows straight from the geometric series formula and simple simplification. We can now multiply the denominator by it's complex conjugate to find:
Comparing real and imaginary parts, we find:
Squaring this equation and letting :
Clearing denominators and solving for gives sine as .
Solution 4
A bit similar to Solution 3. We use because the progression cycles in . So we could rewrite that as .
Similarly, .
Setting complex , we get
.
The important part is the ratio of the imaginary part to the real part. To cancel out the imaginary part from the denominator, we must add to the numerator to make the denominator a difference (or rather a sum) of squares. The denominator does not matter. Only the numerator, because we are trying to find a PROPORTION of values. So denominators would cancel out.
.
Setting , we obtain .
Since because , . Adding up, .
Solution 5 (lots of room for sillies, I wouldn't recommend it)
We notice and
With these, we just quickly find the sum of the infinite geometric series' in and . has 2 parts, the and the parts. The part is: , which can be turned into: , which is . This turns into .
Following the same process as above, we find that the part of is , the part of is , and finally, the part of is .
We convert all 4 of these equations into trig, and we end up getting , we divide by on both numerator and denominator, and we get . We use some trig identities and we get . We factor the denominator into . We cancel out on both numerator and denominator to get . We set as , and we just solve a quadratic in terms of , , cross multiply and simplify, and we get . We can actually factor this to get , which yields the 2 solutions . Since , the latter solution is deemed invalid, and we are left with . Our final answer is .
~ASAB
omg this was definitely the hardest problem on the AIME I
Solution 6
Follow solution 3, up to the point of using the geometric series formula
Moving everything to the other side, and considering only the imaginary part, we get
We can then write , and , (). Thus, we can substitute and divide out by k.
Since , we get , and thus,
-Alexlikemath
See also
2013 AIME I (Problems • Answer Key • Resources) | ||
Preceded by Problem 13 |
Followed by Problem 15 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.